Evaluation of mechanical, optical, and antibacterial properties of metal‐oxide dispersed HDPE nanocomposites processed by rotational molding. Issue 6 (20th April 2022) - Ghanbarpour, Barmak; Moslemi, Amin
Abstract: To investigate the impact of zinc oxide/titanium dioxide nanoparticles on the characteristics of high‐density polyethylene, researchers used the rotational molding technique to produce polymeric nanocomposites. The nanocomposites' morphological, mechanical, optical, as well as biological characteristics, were studied using a range of characterizations. SEM analysis revealed a uniform morphology of ZnO and TiO2 nanoparticles in the polymer matrix, with 80–120 nanometers middle particle dimensions. The existence of ZnO with hexagonal wurtzite form as well as TiO2 with rutile phase was verified by XRD and XRF. Corresponded to the pure polymer, the HDPE‐ZnO/TiO2 nanocomposites' flexural modulus and tensile strength increased, but elongation at break reduced, according to mechanical characterization. UV–visible spectroscopy revealed that the HDPE‐ ZnO/TiO2 nanocomposites showed UV light absorption at wavelengths ranging from 250 to 390 nm. According to antibacterial tests and contact angle measurements, adding metal oxide NPs to HDPE improved hydrophilicity and antibacterial activity. Abstract :